Guía audiovisual de la estación total SOUTH NTS 372 RC (2016)
The audiovisual guide of the Total Station NTS 372 RC; it’s performed by deficiency didactic tools, which hinders the students program learning at university of Quindio; for this reason the video of the total station has as purpose to facilitate the handling of this equipment, for this we do a investigation all lot of chronology surveying of intruments that the laboratory find, inquiring to teachers of the program to determine the importance of the creation of the audiovisual tool, also it’s performed a investigation of variety videos about driving of total station that it has web, achieving so carried out to creation of the channel YouTube with video of the audiovisual guide total station Nts SHOUTH NTS 372 RC.